THE ENGLISH LANGUAGE AND ITS RELEVANCE IN THE MODERN WORLD - Axmatova Farangiz (TADQIQOTLAR, 2026)
Annotation: This article explores the growing importance and relevance of the English language in the modern globalized world. English has become a universal means of communication in education, science, technology, business, tourism, and diplomacy. The paper discusses the historical development of English, its transformation into a global lingua franca, and its influence on international cooperation.